ChemInform Abstract: Functionalization of Anthracene by Strategic Utilization of the Diels—Alder Reaction and the Ring‐Closing Metathesis. Issue 20 (20th May 2014) - Kotha, Sambasivarao; Meshram, Milind
Abstract A new route to synthesize 9, 10‐bridged anthracene derivative (VIII) involving a ring‐closing metathesis reaction as key step is given.